PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (PADA BANDUNG SUPER MODEL SENGKALING KABUPATEN MALANG) - Anis Ulifatul Jannah; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to understand leadership style, motivation and work discipline on the performance of BSM Sengkaling employees in Malang Regency. The sample and population in this study involved 34 people who were general employees of BSM in Sengkaling Regency Malang. The method using is descriptive data analysis that is using the validity, reliability, normality, multicollinearity test, heterocedasticity test, multiple linear analysis test f test, and hypothesis test t. The results showing that simultaneously each variable of leadership style, motivation and work discipline were both positive towards performance, while the partial variable of leadership style did not support performance, motivation did not improve the performance and discipline of power towards performance at BSM Sengkaling Malang Regency .Keywords: Leadership Style, Motivation, Work Discipline and Performance